Collaborative Inquiry for Knowledge Building among Children in Clinical Courses at the Master’s Level at an American College in New York State: A Descriptive Case Study - Vokatis, Barbara (Chowanna, 2023)
In this article, I describe how I teach graduate students who are in-service teachers in our master’s literacy program on how to facilitate inquiry-based learning among school children. This type of learning concentrates on students’ curiosity, asking questions, and investigating problems in collaboration. The teacher in such learning is more of a facilitator working towards helping children in becoming more independent learners. In my role as a teacher educator and coach I have used several resources to develop my own practice of teaching inquiry learning since 2015. I describe how I structure my graduate students’ tutoring for inquiry and how I teach the ways of utilizing literacy teaching strategies and routines, such as shared reading and accountable talk, in order to facilitate children’s knowledge building and their increasing independence in collaborative work. I also describe how my research interests that concentrate around investigating innovative inquiry-based learning spaces has informed this teaching.